Analisis Perbedaan Preferensi Anatara Generasi Y Dan Z Dalam Memilih Kedai Kopi Di Kota Palembang - Priantika, Meisa; Mellita, Dina (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2025)
This study aims to analyze the differences in preferences between Generation Y and Generation Z in choosing coffee shops in Palembang. The research sample consists of 100 respondents, evenly divided into 50 respondents from Generation Y and 50 from Generation Z. The analytical method used is an independent t-test to determine whether there is a significant difference in preferences between the two generations. The results show that there is a significant difference in preferences between Generation Y and Generation Z when selecting a coffee shop. Factors influencing preferences include product quality, shop ambiance, price, and accessibility. These findings are expected to provide insights for coffee shop owners in designing marketing strategies that align with the characteristics of each generation.